Tinjauan Viktimologi terhadap Pemenuhan Hak Korban Pencurian Motor: Studi Kasus Pencurian Motor di Serang - Putri Nurul Aini; Nurul Azkiyah; Najwa Ananda Putri; Ira Septika Putri (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Law enforcement against theft cases not only reviews the position of the perpetrator but also the victim, because the victim has the right to receive protection both materially and immaterially; it is important for law enforcement officers to help victims obtain legal certainty and justice. The purpose of the author's research is to determine the obstacles experienced by victims of motorcycle theft in an effort to obtain their rights as victims and effective strategic efforts to ensure that the rights of victims of motorcycle theft can be fulfilled. Research iThis uses qualitative methods and empirical normative juridical methods. The author conducted interviews as primary data in this article, followed by secondary data in the form of literature from the law (primary source material), books (secondary source material), and scientific journals (tertiary source material). The data obtained shows that there are still quite a lot of obstacles experienced by victims in seeking their rights as victims of motorcycle theft. Victims experience bureaucratic difficulties where the process is complicated; victims also find unprofessional service from law enforcement officers; and victims do not get further information regarding the investigation or get SP2HP. However, there are also effective strategic steps to fulfill the rights of victims of motorcycle theft, namely by increasing access to the legal process through online complaint services and increasing professionalism and responsiveness from law enforcement officers through routine training on handling victims. It can also be done regarding the recovery of victim losses by providing compensation mechanisms and strengthening supervision and prevention by collaborating between the community and the police in the form of environmental security. This shows that there is still a lack of concern from law enforcement officers themselves for victims of motorcycle theft and there is still much that needs to be developed further by the government to improve the welfare of victims of motorcycle theft and government efforts to protect the community from criminal acts of theft.